2017
DOI: 10.18203/2320-6012.ijrms20173585
|View full text |Cite
|
Sign up to set email alerts
|

Role of topical steroid in primary treatment of childhood phimosis

Abstract: Background: Circumcision has been the traditional treatment for phimosis, but with some controversies due to complications. The current study was undertaken to evaluate the effectiveness of topical steroid therapy as primary treatment for childhood phimosis. Methods: A prospective observational study was conducted and a total of 100 patients (age-3 to 12 years) of phimosis were enrolled. The management consisted of topical application of 0.05% betamethasone Ointment for 4 weeks. Those with partial response wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Changole et al . 11 reported poorer outcomes in boys above 5 years of age as compared to younger age group. Ku et al .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Changole et al . 11 reported poorer outcomes in boys above 5 years of age as compared to younger age group. Ku et al .…”
Section: Discussionmentioning
confidence: 88%
“…This study found that the long‐term outcome deteriorated with increasing age, with the lowest success rate (56.6%) in the 8‐ to 12‐year age group. Changole et al 11 . reported poorer outcomes in boys above 5 years of age as compared to younger age group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Continuation of treatment to four weeks results in drug accumulation, increased elasticity of the foreskin and the skin, and improved efficiency. Changole et al ( 13 ) reported that 17.6% of phimosis cases had a remarkable effect in the late stage of treatment. Reddy et al ( 14 ) found that 8.6% of grade 4 and 5 patients responded to continuous therapy for four weeks.…”
Section: Discussionmentioning
confidence: 99%